Taking sides clashing views in business ethics and society - Newton, Lisa H. (New York McGraw-Hill, 2010)
Capitalism and the corporation; Current business issues; Human resources: the corporation and employees; Consumer issues; Global objectives; Environmental policy and corporate responsibility.
ISSN: 95-83859
Includes bibliographical references.
Keywords: Business ethics; Đạo đức học; Môi trường